Acculturating Contexts and Anglo Opposition to Immigration in the United States. Issue 2 (30th November 2012) - Newman, Benjamin J.
<x xml:space="preserve">Abstract</x> This article explores the impact of novel change in the ethnic composition of Americans' local context on their attitudes toward immigrants and immigration policy preferences. Adapting the "defended‐neighborhoods hypothesis" regarding residential integration and black‐white interracial relations to the context of immigration and intercultural relations, this article advances the acculturating‐contexts hypothesis. This hypothesis argues that a large influx of an immigrant group will activate threat among white citizens when it occurs in local areas where the immigrant group had largely been absent. This theoretical argument is explored within the context of Hispanic immigration and tested using national survey and census data. This article demonstrates that over‐time growth in local Hispanic populations triggers threat and opposition to immigration among whites residing in contexts with few initial Hispanics but reduces threat and opposition to immigration among whites residing in contexts with large preexisting Hispanic populations.